کاریگەری لێژی لەسەر دیاریکردنی گۆشەی گونجاو و ئاڕاستەی گونجاوی پانێڵی خۆر (solar panel) لە ناوچە چیاپێچ ئاڵۆزەکانی پارێزگای سلێمانی - احمد, پ.د. سۆران حمە امین; احمد, د. شۆخان محمد; رشید, خوێدکاری ماستەر/ شیراز عوسمان (Sulaimani Journal for Humanities, 2023)
The aim of this study is to analyze the effect of slope on solar energy production in terms of the effect on the direction and angle of the panels and determine the appropriate direction and angle facing the sun to achieve maximum solar energy production during production, Slope is considered to be one of the most important factors affecting solar energy generation potential, especially in terms of degree and slope direction in the study area. The amount of sunlight falling on the solar panels depends on the angle between the panels and the horizontal level. Therefore, this angle must be chosen carefully so that the panels can absorb the maximum amount of sunlight. Changing the angle of solar panels to an appropriate angle according to the month and seasons increases the amount of energy production. Changing the angles in the study area an average of 12 times a year increases the energy value by 30% compared to panels Fixed throughout the year, but this change cannot always occur because the operating costs are economically high, so it is better to place at a fixed angle according to the appropriate face direction and latitude to suit all seasons. (35°:26': 44") and (36°:23':49") North and longitude (44°:35': 47") and (46°:20':48") East, the appropriate angle throughout the year at the study area is (37°) while the appropriate monthly latitude angle is different for each month. The lowest latitude angle of the solar panel is in June with an angle of (13°.60) and the highest latitude angle is in December with an angle of (59°). The appropriate facing directions are south and southwest, with the product of these two directions being higher than the other d in other directions.